The global nephrology workforce: emerging threats and potential solutions! - Sharif, Muhammad U. (Clin Kidney J, 2016)
Amidst the rising tide of chronic kidney disease (CKD) burden, the global nephrology workforce has failed to expand in order to meet the growing healthcare needs of this vulnerable patient population. In truth, this shortage of nephrologists is seen in many parts of the world, including North America, Europe, Australia, New Zealand, Asia and the African continent. Moreover, expert groups on workforce planning as well as national and international professional organizations predict further reductions in the nephrology workforce over the next decade, with potentially serious implications. Although the full impact of this has not been clearly articulated, what is clear is that the delivery of care to patients with CKD may be threatened in many parts of the world unless effective country-specific workforce strategies are put in place and implemented. Multiple factors are responsible for this apparent shortage in the nephrology workforce and the underpinning reasons may vary across health systems and countries. Potential contributors include the increasing burden of CKD, aging workforce, declining interest in nephrology among trainees, lack of exposure to nephrology among students and residents, rising cost of medical education and specialist training, increasing cultural and ethnic disparities between patients and care providers, increasing reliance on foreign medical graduates, inflexible work schedules, erosion of nephrology practice scope by other specialists, inadequate training, reduced focus on scholarship and research funds, increased demand to meet quality of care standards and the development of new care delivery models. It is apparent from this list that the solution is not simple and that a comprehensive evaluation is required. Consequently, there is an urgent need for all countries to develop a policy framework for the provision of kidney disease services within their health systems, a framework that is based on accurate projections of disease burden, a full understanding of the internal care delivery systems and a framework that is underpinned by robust health intelligence on current and expected workforce numbers required to support the delivery of kidney disease care. Given the expected increases in global disease burden and the equally important increase in many established kidney disease risk factors such as diabetes and hypertension, the organization of delivery and sustainability of kidney disease care should be enshrined in governmental policy and legislation. Effective nephrology workforce planning should be comprehensive and detailed, taking into consideration the structure and organization of the health system, existing care delivery models, nephrology workforce practices and the size, quality and success of internal nephrology training programmes. Effective training programmes at the undergraduate and postgraduate levels, adoption of novel recruitment strategies, flexible workforce practices, greater ownership of the traditional nephrology landscape and enhanced opportunities for research should be part of the implementation process. Given that many of the factors that impact on workforce capacity are generic across countries, cooperation at an international level would be desirable to strengthen efforts in workforce planning and ensure sustainable models of healthcare delivery.